2022
DOI: 10.3390/nano12121976
|View full text |Cite
|
Sign up to set email alerts
|

Properties of SS304 Modified by Nickel–Cobalt Alloy Coating with Cauliflower-Shaped Micro/Nano Structures in Simulated PEMFC Cathode Environment

Abstract: This study presents the corrosion behavior and surface properties of SS304 modified by electrodeposited nickel–cobalt (Ni–Co) alloy coating with cauliflower-shaped micro/nano structures (Ni–Co/SS304) in the simulated PEMFC cathodic environment. The hydrophobicity of the as-prepared Ni–Co alloy coating can be improved simply by low-temperature annealing. The morphology and composition of the Ni–Co/SS304 were analyzed and characterized by SEM, EDS, XRD, and XPS. The polarization, wettability, and ICR tests were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In the Ni 2p spectrum (Figure e), the peak in fresh 6% Ni–4% Co/char at 852.6 and 869.9 eV were ascribed to Ni 0 , which showed that the metallic Ni mainly existed in the shape of Ni 0 . The new peaks for Ni 2+ at 862.3 eV were observed on the spent 6% Ni–4% Co/char ( N = 1) because of a small amount of Ni being oxidized to NiO, which corresponded to the result of XRD . For the Co 2p spectrum (Figure f), the peaks at 778.0 and 794.2 eV were attributed to Co .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the Ni 2p spectrum (Figure e), the peak in fresh 6% Ni–4% Co/char at 852.6 and 869.9 eV were ascribed to Ni 0 , which showed that the metallic Ni mainly existed in the shape of Ni 0 . The new peaks for Ni 2+ at 862.3 eV were observed on the spent 6% Ni–4% Co/char ( N = 1) because of a small amount of Ni being oxidized to NiO, which corresponded to the result of XRD . For the Co 2p spectrum (Figure f), the peaks at 778.0 and 794.2 eV were attributed to Co .…”
Section: Resultsmentioning
confidence: 98%
“…79 Gai et al and Ren et al both found that the modified char-supported catalysts exhibited higher catalytic activity due to the outstanding graphitized and layered delocalized structures. 46,80 In the Ni 2p spectrum (Figure 6e), the peak in fresh 6% Ni− 4% Co/char at 852.6 and 869.9 eV were ascribed to Ni 0 , 81 which showed that the metallic Ni mainly existed in the shape of Ni 0 . The new peaks for Ni 2+ at 862.3 eV were observed on the spent 6% Ni−4% Co/char (N = 1) because of a small amount of Ni being oxidized to NiO, which corresponded to the result of XRD.…”
Section: Effects Of Catalytic Reforming Temperature and Promoter Co L...mentioning
confidence: 98%
See 1 more Smart Citation